2021
DOI: 10.1021/acsnano.1c05725
|View full text |Cite
|
Sign up to set email alerts
|

A Superlattice-Stabilized Layered CuS Anode for High-Performance Aqueous Zinc-Ion Batteries

Abstract: Rechargeable aqueous zinc ion batteries (AZIBs) are attracting extensive attention owing to environmental friendliness and high safety. However, its practical applications are limited to the poor Coulombic efficiency and stability of a Zn anode. Herein, we demonstrate a periodically stacked CuS-CTAB superlattice, as a competitive conversion-type anode for AZIBs with greatly improved specific capacity, rate performance, and stability. The CuS layers react with Zn2+ to endow high capacity, while CTAB layers serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 33 publications
1
89
0
Order By: Relevance
“…This might be attributed to the fact that CTAB intercalated into MoS 2 and the weak Coulomb interaction between layers therefrom. 25 The SXRD patterns indicate the enlarged interlayer spacing of MoS 2 −CTAB and the successful formation of an organic−inorganic superlattice structure. In addition, different amounts of CTAB could affect the formation process of the structure, and the XRD peak of the superlattice could be significantly observed above 9.6 × 10 −4 mol CTAB.…”
Section: Resultsmentioning
confidence: 96%
“…This might be attributed to the fact that CTAB intercalated into MoS 2 and the weak Coulomb interaction between layers therefrom. 25 The SXRD patterns indicate the enlarged interlayer spacing of MoS 2 −CTAB and the successful formation of an organic−inorganic superlattice structure. In addition, different amounts of CTAB could affect the formation process of the structure, and the XRD peak of the superlattice could be significantly observed above 9.6 × 10 −4 mol CTAB.…”
Section: Resultsmentioning
confidence: 96%
“…reported that the construction of an organic–inorganic superlattice structure can stabilize the reversible transition process of CuS, thereby achieving enhanced cycle stability (≈ 87.6% capacity retention over 3400 cycles) and reliable capacity. [ 31 ] These progressional results indicate that advanced design strategies such as defect engineering or heterogeneous interfaces would be beneficial to ion dynamics and structural stability, respectively, thereby modulating the Zn 2+ storage mechanism of Cu‐TMC anodes as well as improving one or more aspects of electrochemical performance. Therefore, it is foreseeable that the combination of multiple optimization strategies will synergistically improve the anode performance in AZIBs, which will also reveal the similarity and divergence of intrinsic electrochemical behaviors and performances for Zn 2+ storage in Cu‐based chalcogenides and that is worth exploring.…”
Section: Introductionmentioning
confidence: 99%
“…3f, the proposed TiTe 2 electrode has a high capacity and long cycling life among the state-of-the-art low-voltage electrodes for RAZBs. 23,25–29,38–40…”
Section: Resultsmentioning
confidence: 99%
“…3f, the proposed TiTe 2 electrode has a high capacity and long cycling life among the state-of-the-art low-voltage electrodes for RAZBs. 23,[25][26][27][28][29][38][39][40] The galvanostatic intermittent titration technique (GITT) and electrochemical impedance spectroscopy (EIS) were carried out to probe the kinetic process. As shown in Fig.…”
Section: Electrochemical Performance and Kineticsmentioning
confidence: 99%
See 1 more Smart Citation